Structure, function and performance of Early Warning Alert and Response Network (EWARN) in emergencies in the Eastern Mediterranean Region. (April 2021) - Mala, Peter; Abubakar, Abdinasir; Takeuchi, Akiko; Buliva, Evans; Husain, Farah; Malik, Mamunur Rahman; Tayyab, Mohammed; Elnoserry, Sherein
Highlights: The outbreak detection function was undermined by inclusion of non-epidemic diseases. Adoption of electronic platforms expanded coverage of hard-to-reach areas. Conflict emergencies limited coverage, despite progress due to electronic solutions. The EWARN is being retained far longer than expected in protracted emergencies. Abstract: Introduction: The Eastern Mediterranean Region (EMR) has experienced several protracted humanitarian crises. The affected population are served by eight Early Warning Alert and Response Network (EWARN) systems for outbreak detection and response. This study aimed to compare structure, function and performance of the systems' adherence to current guidance, and noted emerging lessons. Methods: This study included a review of published and unpublished literature, a structured survey and interviews. Results: Findings showed that all systems adhered to basic EWARN structure. Four of eight systems had electronic platforms, while one was implementing one. Regarding key EWARN function of outbreak detection: of the 35 health conditions, 26 were communicable diseases and nine were non-communicable; two systems focused on epidemic-prone diseases. Half the systems achieved ≥60% population coverage, five achieved ≥80% reporting timeliness, six achieved ≥80% reporting completeness, and seven achieved verification of ≥80% of alerts of suspected outbreaks. Conclusion: The findings showed that the systems followed the EWARN structure, while increasing adoption of electronic platforms. Performance, including timeliness and completeness of reporting, and timely verification of alerts were optimal for most of the systems. However, population coverage was low for most of the systems, and the EWARN's primary focus of outbreak detection was undermined by the increasing number of non-epidemic diseases.